Xiloglucanas e galactomananas de leguminosas: interação com lectinas D-galactose-ligantes - Landim, Patrícia Gadelha de Castro (2007)
Polysaccharides are found in large quantity in seeds and they represent the main compounds of cell wall or reservoir. Among reservoir compounds, it included cotyledonary xyloglucans and endospermic galactomannans. The xyloglucans are made of a main chain of β-D-(1→4)-glucan with α-(1→6) ramifications of D-xylopyranoside or β-D-galactopyranoside-(1→2)-D-xylopyranoside residues. Endospermic galactomannans are polimeric chains of β-D-mannopyranosil (1→4) and replaceabled in O-6 for units of α-D-galactopyranosil. The aim of this work is investigate the interaction of xyloglucans and galactomannans with galactose bounding lectins and show the possibility of the usage of these polysaccharides as cheap and useful chromatographic matrices for isolation and determination of anomeric specificity of galactose bounding lectins. The interactions of lectins from seeds of Artocarpus integrifolia (frutalin), Artocarpus incisa (jacalin), Ricinus communis (ricin) e Arachis hypogaea (PNA) were performed with coluns of xyloglucans of seeds from Copaifera langsdorffii, Mucuna sloanei and Hymenaea courbaril (MC, MMu, MJ, respectively) and galactomannans from Mimosa scabrella, Stryphnodendron barbatiman, Adenanthera pavonina and Dimorphandra mollis (MM, MS, MA; MD, respectively). The galactomannans showed the best colun interaction capacity for the jacalin (MA – 0,92 mg ; MM – 1,48 mg ; MD –0,88 mg ; MS – 0,83 mg) and frutalin (MA – 0,99 mg ; MM – 1,09 mg ; MD - 0,94 mg ; MS - 0,85 mg) lectins. Remarkably the M. scabrella galactomannan showed the best colun interaction among all lectins analysed. On the other hand, ricin was better hold in coluns made of xyloglucan (MMu – 2,17 mg ;MJ – 1,30 mg; MC – 2,83 mg). For PNA lectin, differences were detected in colun interaction capacity. The best colun interaction was with the M. sloanei matrix (0,12 mg) for PNA lectin. All coluns were fill with sample extract of flour from seeds and hemagglutination assays was performed with PI and PII. In these assays, hemagglutination activity was detected in both PI and PII from the coluns. For ricin, toxic activity was made and it was detected for all obtained chromatographic samples. With SDS-PAGE it was possible confirmed the purification of the studied lectins. The bands in polyacrilamid gel were the same for the lectins purified. In conclusion, it can be suggested the usage of xyloglucans and galactomannans for isolation, purification and determination of anomeric specificity of galactose-bounding lectins.